(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2022)
Studies on the nutritional status of habanero pepper (Capsicum chinense Jacquin) in relation to organic fertilization are still incomplete and preliminary. To evaluate the effects of organic fertilizer doses, produced from family farming wastes, a greenhouse experiment was conducted at the Universidade Federal Rural da Amazônia, Belém, Pará, Brazil. The experiment followed an entirely randomized design, with five treatments and four repetitions. Each experimental plot was composed of a pot with a volume of 3.6 dm3 of soil, in which the seeds were sown. Five doses of organic fertilizer were tested (0%, 15%, 30%, 45% and 60%) composed of a mixture of chicken manure (10%), duck manure (20%), cassava peel (15%), cassava leaf (15%), bean straw (15%), rice husk (15%) and corn cob (10%), mixed in volumetric proportions in the substrate. A Yellow Latosol of sandy texture was sampled from the superficial layer (0-20 cm). The best results were achieved at 103 days using the 60% dose of organic manure. The content and accumulation of macronutrients in leaf tissues showed the following order: N˃K≥S˃Ca≥Mg˃P and N˃K˃S˃Mg˃Ca˃P. In the fruits the order was followed: N˃K˃S˃P˃Mg˃Ca.